Cellular Interactions of the Cytolethal Distending Toxins from Escherichia coli and Haemophilus ducreyi - Gargi, Amandeep (American Society for Biochemistry and Molecular Biology, 2013)
The cytolethal distending toxins (CDTs) compose a subclass of intracellularly acting genotoxins produced by many Gram-negative pathogenic bacteria that disrupt the normal progression of the eukaryotic cell cycle. Here, the intoxication mechanisms of CDTs from Escherichia coli (Ec-CDT) and Haemophilus ducreyi (Hd-CDT), which share limited amino acid sequence homology, were directly compared. Ec-CDT and Hd-CDT shared comparable in vitro DNase activities of the CdtB subunits, saturable cell surface binding with comparable affinities, and the requirement for an intact Golgi complex to induce cell cycle arrest. In contrast, disruption of endosome acidification blocked Hd-CDT-mediated cell cycle arrest and toxin transport to the endoplasmic reticulum and nucleus, while having no effects on Ec-CDT. Phosphorylation of the histone protein H2AX, as well as nuclear localization, was inhibited for Hd-CdtB, but not Ec-CdtB, in cells expressing dominant negative Rab7 (T22N), suggesting that Hd-CDT, but not Ec-CDT, is trafficked through late endosomal vesicles. In support of this idea, significantly more Hd-CdtB than Ec-CdtB co-localized with Rab9, which is enriched in late endosomal compartments. Competitive binding studies suggested that Ec-CDT and Hd-CDT bind to discrete cell surface determinants. These results suggest that Ec-CDT and Hd-CDT are transported within cells by distinct pathways, possibly mediated by their interaction with different receptors at the cell surface.